Do Degree Programs Affect Health Profession Students' Attitudes and Opinions Toward Vaccinations? An Italian Multicenter Study - Gianluca Voglino; Andrea Barbara; Giulia Dallagiacoma; Omar Enzo Santangelo; Sandro Provenzano; Vincenza Gianfredi (Safety and Health at Work, 2022)
Background: Healthcare workers' attitudes toward vaccination have been widely described in the literature, but a restricted amount of studies assessed healthcare students' knowledge, attitudes, and opinions on this issue. This study aimed to estimate the influence of a degree course on knowledge and immunization behavior among healthcare students and to compare medical students with students from other health profession degree programs to identify possible differences. Methods: A multicenter, cross-sectional study was performed in 2018 in 14 Italian Universities (3,131 students were interviewed). A validated questionnaire was used to assess knowledge, attitudes, and opinions toward vaccinations, with a specific focus on influenza vaccine and attitudes toward mandatory vaccination policies. Statistical software STATA® 14 was used. Results: Significant differences were recorded between medical students and other healthcare students. The intention to get vaccinated against influenza during the next season and having been vaccinated in the previous season was higher in the medical group (p < 0.001). In the group of students of other health professions, we registered a lower probability of identifying themselves as a high-risk group for contracting infectious diseases as a consequence of their profession and health status (aOR 0.49; CI95%: 0.40–0.60) and an increased likelihood of defining their level of knowledge on vaccine-preventable diseases and related vaccinations as “insufficient/sufficient/fair” (aOR 1.31; CI95%: 1.11–1.56). Conclusions: Results show several differences between medical students and students of other health professions when it comes to vaccination knowledge, attitudes, and perceptions, as well as a general low tendency to be vaccinated against influenza.